Penerapan Artificial Intelligence (AI) dalam Dunia Pendidikan - David Saputra (Jurnal Sains dan Teknologi Indonesia, 2025)
The role of Artificial Intelligence (AI) in education is rapidly expanding, serving as a transformative instrument to enhance both instructional and administrative practices. Through AI, students can experience customized learning pathways, receive adaptive feedback, and access automated support systems. Technologies like virtual tutors and AI-based chatbots not only foster interactive learning but also improve efficiency in managing educational tasks. Nevertheless, its application faces obstacles, including concerns over information security, unequal access to technology, and educators’ preparedness. Thus, implementing AI in education should be accompanied by strategic policies, robust infrastructure, and ongoing teacher training to achieve inclusive and effective educational progress.